Seabed Morphology and Geohazard Assessment for Subsea Pipeline Routing based on MBES and Seismic Data: A Case Study of Teluk Palabuhanratu, Indonesia - Salsabila, Chairunisyah Putri; Idarwati; Salni, Muhammad Alfath Salvano; Rasyid, Faris Nauval (UIR PRESS, 2026)
To support the development of subsea pipeline infrastructure across Java, there is a need to assess geohazard potential in Teluk Palabuhanratu. The aim of this study is to characterize seabed morphology and evaluate its implications for geohazard potential for subsea pipeline routes. The method employed consists of morphometric analysis based on digital bathymetric model (DBM) that is derived from multibeam echosounder (MBES), delineation of seabed morphological units by integrating DBM with seismic interpretation, and geohazard assessment based on morphometric parameters and morphological units. Seabed morphology is predominantly characterized by very gentle to gentle slopes, near-planar curvature, and low roughness, while localized zones of steep slopes, complex curvature, and high roughness are associated with faults, submarine landslides, and mud volcanoes. Ten morphological units were identified, including slopes, ridges, knolls, channels, basin floors, sand ridges, mounds, valleys, gullies, and landslides. The geocost-based geohazard assessment indicates a spectrum of hazard potential ranging from low to high for subsea pipeline. High hazard levels are associated with steep slopes, high roughness, and morphological units influenced by erosion and mass-transport processes, such as gullies, valleys, and fault-associated ridges.